Rediscovery and redescription of Scaphisoma nigrofasciatum Pic (Coleoptera: Staphylindae: Scaphidiinae): a remarkable new record from a distant continent - Groll, Elisa Von (Zootaxa, 2023)
Scaphisoma nigrofasciatum Pic is a shining fungus beetle whose distribution was recorded from the Asian continent and three insular African countries. This paper presents a new record of this species from Brazil. In this paper, photographs of specimens from both Brazil and Asia are provided, accompanied by a brief new redescription. A preliminary hypothesis suggests that this species may have been introduced to Brazil alongside flamboyant trees.